Electrical weed control in organic highbush blueberry: influence of operational speed and number of applications on weed control - Baccin, Luisa C.; Moretti, Marcelo L. (Frontiers in Agronomy, 2025)
Weed control remains a critical challenge for organic blueberry producers in the Pacific Northwest, where most U.S. organic blueberry hectarage is concentrated. Electrical weed control (EWC) offers a nonchemical alternative by applying high-voltage currents to plant foliage, disrupting vascular function through heat-induced tissue damage. This study evaluated how operational speed and the number of EWC applications influence weed control efficacy across five field studies in certified organic blueberry fields in Oregon, using two types of commercial EWC equipment. Slower speeds (0.5–1 km h-1; 69–35 kJ m-2) achieved the highest efficacy, providing >80% weed control at 28 days after initial treatment (DAIT) and reducing biomass by up to 73% compared to nontreated. Sequential applications were critical for sustained control: two applications at 2 or 4 km h-1 (17–9 kJ m-2 per application) provided 77–83% weed control at 42 DAIT. Species-specific responses were observed, with northern willowherb (Epilobium ciliatum) and Pennsylvania smartweed (Persicaria pensylvanica) being more sensitive to EWC with 85–100% control at 42 DAIT, while tall fescue (Festuca arundinacea) and sharppoint fluvellin (Kickxia elatine) required multiple treatments and higher energy doses (≥24 kJ m-2) to reach 67–73% control at the same period. In a combined methods study long-term efficacy declined with single-application treatments, with control dropping below 20% by 56 DAIT, whereas sequential applications sustained >40% control. These results demonstrate that EWC provides effective nonchemical weed management in organic blueberry production, with operational speed and sequential applications key to maintain high levels of weed control.